Exploring Time Use Patterns and Influences on Unpaid Work: Findings from the 2019 Indian Time Use Survey - Aastha (Economics, Business, Accounting & Society Review, 2024)
This paper aims to investigate the gender patterns and determinants of unpaid work within the context of India. The primary objectives are two-fold: first, to analyze the time utilization patterns of both men and women in paid, unpaid, and leisure activities, and second, to explore the factors influencing unpaid work. The methodology employed in this study relies on secondary data, specifically the unit-level data from the Indian Time Use Survey conducted in 2019. Descriptive analysis utilized to dissect time allocation patterns. Additionally, the Ordinary Least Square (OLS) method has been employed to examine the relationships between unpaid time and other explanatory variables. The findings of this study reveal significant disparities in unpaid work between men and women, irrespective of whether they reside in urban or rural areas. Women consistently allocate more time to unpaid work than men. Furthermore, the research identifies key determinants of unpaid time, including gender, marital status, level of education, and usual employment status, all of which play pivotal roles in shaping time allocation patterns.  In conclusion, this study sheds light on the intricate dynamics of unpaid work, emphasizing its gendered nature and the multifaceted factors that underpin these disparities. Understanding these patterns and determinants is crucial for informing policies aimed at promoting gender equality and addressing domestic and care-related responsibilities.